Improving Allergy Documentation: A Retrospective Electronic Health Record System–Wide Patient Safety Initiative. Issue 1 (2nd January 2022) - Li, Lily; Foer, Dinah; Hallisey, Robert K.; Hanson, Carol; McKee, Ashley E.; Zuccotti, Gianna; Mort, Elizabeth A.; Sequist, Thomas D.; Kaufman, Nathan E.; Seguin, Claire M.; Kachalia, Allen; Blumenthal, Kimberly G.; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Documentation of allergies in a coded, non–free-text format in the electronic health record (EHR) triggers clinical decision support to prevent adverse events. Health system-wide patient safety initiatives to improve EHR allergy documentation by specifically decreasing free-text allergy entries have not been reported. The goal of this initiative was to systematically reduce free-text allergen entries in the EHR allergy module. Methods: We assessed free-text allergy entries in a commercial EHR used at a multihospital integrated health care system in the greater Boston area. Using both manual and automated methods, a multidisciplinary consensus group prioritized high-risk and frequently used free-text allergens for conversion to coded entries, added new allergen entries, and deleted duplicate allergen entries. Environmental allergies were moved to the patient problem list. Results: We identified 242, 330 free-text entries, which included a variety of environmental allergies (42%), food allergies (18%), contrast media allergies (13%), "no known allergy" (12%), drug allergies (2%), and "no contrast allergy" (2%). Most free-text entries were entered by medical assistants in ambulatory settings (34%) and registered nurses in perioperative settings (20%). We remediated a total of 52, 206 free-text entries with automated methods and 79, 578 free-text entries with manual methods. Conclusions: Through this multidisciplinary intervention, we identified and remediated 131, 784 free-text entries in our EHR to improve clinical decision support and patient safety. Additional strategies are required to completely eliminate free-text allergy entry, and establish systematic, consistent, and safe guidelines for documenting allergies.